Perbedaan Sikap dan Pengalaman Terhadap Kepedulian Lingkungan Sesuai dengan Pendidikan pada Anak Pusat Kota dan Anak Pedesaan (PIAUD IAIN Kudus, 2021)
The problem of natural damage in the territory of Indonesia is getting worse, various human acts in exploiting excessive natural resources have caused natural disasters that damage the environment. Prevention and mitigation of damage to the natural environment requires cooperation between communitties, on of which is to install a sense of caring attitude towards early childhood both in city centre and village. The purpose of this research to see what is related to environmental awareness in accordance with the education givent to children in city centre and village. The research method used by researchers is a qualitative research method with a type of case study. The data techniques used were observation, interviews, and documentation. The subjects of this study were five students of Kindergarten Ceria Demangan and five students Al Fatih. The result of this research is the attitude of caring for ehe enviroment in city centre children who have a higher sensitivity than rural children, but the environmental experience of rural children has a higher experiencecompared to children in the city centre.